Analysis of relationship between strength compression and young modulus of red brick and white brick on application of strength and stiffness building construction with linear regression test - Jefrizal Sihombing; Rayhan Farisi R; Risal Ardiansyah P (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2020)
Building walls in Indonesia are often cracked due to natural and human factors. Therefore the building walls must have high strength and rigidity. The strength and rigidity of a material are interconnected. The higher the value of the strength of the material, the higher the stiffness value. And in Indonesia, in general, using white bricks and red bricks. This experiment aims to analyze and relate the compressive strength values ​​with the modulus of young white bricks and red bricks with linear regression tests to determine suitable building materials for building wall construction. The compressive strength and modulus of young values ​​are measured by means of a Vesta tester by recording weight dial and strain dial for each 10kN increase. Based on the elasticity and compressive strength test data, the compressive strength and modulus values ​​of young bricks are obtained. The value of modulus young red brick, that is, the value of one sample red brick is (0-130) MPa. The value of the two red brick samples (0-20.62) MPa. The value of the red brick sample is three (0-3.82) MPa. While the modulus value of young white brick sample one is (0-44.86) MPa. The supply of two sample white bricks is (0-33.81) MPa. The value of the three sample white bricks is (0-77.97) N / m2. While the compressive strength value of white brick sample one is (0-3.27) MPa. The value of sample two white bricks is (0-3.44) MPa. The value of the three sample white bricks is (0.01-3.39) MPa. Whereas the compressive strength value of red brick sample one is (0-2.77) MPa. The value of red brick sample two is (0-2.14) MPa. The value of the three sample red bricks is (0-0.60) MPa. The tendency of compressive strength and modulus young values ​​are directly proportional.